The Effect of Mounted Dumble Load Training on Turbo Throwing Ability in Students SD Negeri 19 Tebing Tinggi - Ramadita, Prayogi; Wardiah, Dessy; Manullang, Jujur Gunawan (Journal of Social Work and Science Education, 2023)
Turbo throwing is one of the throwing number activities in kid’s athletics, which is the activity of throwing with one hand to reach a certain distance. To increase the strength of the hand muscles it is necessary to do certain forms of exercise . The exercise used in this study is the mounted dumble load exercise The research method is quantitative using the research method “pre-experimental planning” ie (pre-testing of one group -planning after the test). The population at this study had a total of 24 people. The sample in this study amounted to 24 people. Based on the results of hypothesis testing, the calculated t value = 8.250 > t table = 1.714 with a significant level ( α : 0.05), so it was rejected and accepted, so it can be concluded that the study with the title “The effect of mounted dumble load training on turbo throwing ability in extracurricular athletic students at SD Negeri 19 Tebing Tinggi” had a significant effect.